2010
DOI: 10.1007/s12648-010-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Lattice thermal conductivity of skutterudite compounds

Abstract: A generalized expression is used on the basis of relaxation time approximation to facilitate calculation of lattice thermal conductivity of dielectric materials as well as skutterudite family consists of compounds of the form AB 3 . It is assumed that phonon scattering processes are independent and is represented by frequency dependent relaxation times. The contributions of normal three phonon scattering processes are included explicitly as redistribution of phonon momentum between two oscillation branches is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The usage of Piper nigrum and Allium cepa was very common for curing eye diseases, indigestion, constipation, wounds (Tiwari and Pande, 2010) insect problems (Saikia and Borthakur, 2010) and fever (Nag et al, 2007) (Nag et al, 2007) were reported to have ethnoveterinary medicinal values in many places of India. Further study and promotion of ethnoveterinary medicine is bound to help the communities conserve information and integrate select practices into rural animal healthcare services.…”
Section: International Letters Of Natural Sciences Vol 24mentioning
confidence: 99%
“…The usage of Piper nigrum and Allium cepa was very common for curing eye diseases, indigestion, constipation, wounds (Tiwari and Pande, 2010) insect problems (Saikia and Borthakur, 2010) and fever (Nag et al, 2007) (Nag et al, 2007) were reported to have ethnoveterinary medicinal values in many places of India. Further study and promotion of ethnoveterinary medicine is bound to help the communities conserve information and integrate select practices into rural animal healthcare services.…”
Section: International Letters Of Natural Sciences Vol 24mentioning
confidence: 99%
“…The rhizome of Curcuma is a source of a yellow dye and has been historically used as spices, food preservatives, flavoring agent, and household remedy for treatment of many diseases [2]. They have been used as traditional medicines for the treatment of enlarged liver, spleen, stomach ulcer, diabetes, cough, hepatic disorders, chest pain, skin diseases, boils, blood purifier and rheumatism [3][4][5][6]. Curcuma longa is a tropical rhizomatous cultivated most extensively in India, followed by Bangladesh, China, Thailand, Cambodia, Malaysia, Indonesia and the Philippines.…”
Section: Introductionmentioning
confidence: 99%